A Story of Emergent Leadership: Lived Experiences of Nurses in a Critical Access Hospital - Judith Maria Paré; Polly Petersen; Dayle Boynton Sharp (Rural Nurse Organization; Binghamton University, 2017)
Purpose: The purpose of this study was to understand the lived experiences of nurses working in a predominantly rural care setting. In order to meet the needs of an aging population with multiple comorbidities, it is essential for leaders to understand the strategies to recruit and retain highly qualified nurses in CAHs settings. Sample: Nine registered nurses working both full and part time with one to 40 years of experience participated in the interview process that queried their attitudes regarding working in a rural setting. Findings: Five major themes included self-reliance, social responsibility, empathy, isolation, and emergent leadership. Conclusions: The findings from this study support the notion that there is not a universal response to the lived experience of nurses working in CAHs. The unique needs of each nurse should be considered to enhance the practice environment and diminish experiences that result in feelings of isolation. Isolation impacted the five themes; if nurses are not able to maintain current knowledge and skills in a supportive environment, their self-reliance is compromised. Keywords: Rural, Nursing, Self-reliance, Emerging leader DOI:  http://dx.doi.org/10.14574/ojrnhc.v17i2.454